Information technologies in medicine. 5th International Conference, ITIB 2016 Kamień Śla̜̜ski, Poland, June 20-22, 2016 Proceedings /: 5th International Conference, ITIB 2016 Kamień Śla̜̜ski, Poland, June 20-22, 2016 Proceedings. Volume 2 : (2016) - Unknown
No abstract available